2017
DOI: 10.3390/inorganics5020038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of LiAlH4 Nanoparticles Leading to a Single Hydrogen Release Step upon Ti Coating

Abstract: Lithium aluminum hydride (LiAlH 4 ) is an interesting high capacity hydrogen storage material with fast hydrogen release kinetics when mechanically activated with additives. Herein, we report on a novel approach to produce nanoscale LiAlH 4 via a bottom-up synthesis. Upon further coating of these nanoparticles with Ti, the composite nanomaterial was found to decompose at 120 • C in one single and extremely sharp exothermic event with instant hydrogen release. This finding implies a significant thermodynamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…In the case of LiAlH 4 , the improved desorption kinetics was reported by the doping of Ti catalyst using mechanically milling [10][11][12]. Recent study also reported a single step hydrogen release of LiAlH 4 , which was induced by the synergetic effects of Ti catalytic coating and nanosizing effects [13]. Although the rehydrogenation of the desorbed material was not achieved in the milled sample, the regeneration of LiAlH 4 from LiH and Ti-catalyzed Al was possible through the solution synthesis approach using THF and Me 2 O [14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…In the case of LiAlH 4 , the improved desorption kinetics was reported by the doping of Ti catalyst using mechanically milling [10][11][12]. Recent study also reported a single step hydrogen release of LiAlH 4 , which was induced by the synergetic effects of Ti catalytic coating and nanosizing effects [13]. Although the rehydrogenation of the desorbed material was not achieved in the milled sample, the regeneration of LiAlH 4 from LiH and Ti-catalyzed Al was possible through the solution synthesis approach using THF and Me 2 O [14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…However, its practical use is hindered by the poor reversibility and excessive temperature required for hydrogen release. 11 One of the problems is to stabilize the hydride nanoparticles, being the use of surfactants in the synthesis of LiBH4, 12,13 an alternative, but with little support and divulgation. Alanates, borohydrides, and amides are complex hydrides with high concentrations of hydrogen that have been actively investigated for materials-based hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 absorption/desorption kinetics of alanates have been improved by the addition of a small amount of Ti species, and the catalytic mechanism has been discussed. 13,14 In recent years, boron nitride addition has been reported as one of the strategies to improve the absorption/desorption properties of complex hydrides. For instance, remarkable absorption/desorption properties have been achieved in LiBH 4 /BN composites, probably because of the enhancement of H 2 dissociation, H − diffusion, and Li + diffusion by nanoscale BN.…”
Section: Introductionmentioning
confidence: 99%